Surface quality of printed porous materials for permeability rig calibration. Issue 5 (4th April 2022) - Bodaghi, M.; Mobin, M.; Ban, D.; Lomov, S. V.; Nikzad, M.
ABSTRACT: The enhancement of surface roughness of a textile-like porous medium fabricated by 3D printing techniques is crucial for the repeatability of permeability experiments from test to test. This paper aims at comparison of the surface quality of textile-like porous media fabricated by Stereolithography (SLA), Fused Deposition Modeling (FDM), and Multi Jet Fusion (MJF) 3D printing techniques. Hence, a 3D optical profilometer was used to evaluate the 3D areal surface texture parameters of samples according to ISO 25178. The results revealed that SLA technique produces the smoothest surface with the lowest deviation in the measured values of the surface characteristics. Also, the surface parameters such as the average roughness (Sa) and root mean square (RSM) roughness (Sq) of the top surface of MJF samples are lower than those measured for FDM sample. Furthermore, filling pattern of the FDM technique as a trajectory filament-based AM process results in rougher horizontal surfaces compared to those produced by a non-trajectory powder-based process such as MJF.